Economic Growth and CO2 Emissions: Investigating the Environmental Kuznets Curve Hypothesis in Algeria - Lacheheb, Miloud; Abdul Rahim, Abdul Samad; Sirag, Abdalla (International Journal of Energy Economics and Policy, 2015)
This study examines the existence of environmental Kuznets Curve (EKC) hypothesis between economic growth and CO2 emission in Algeria for the period 1971-2009 using Autoregressive Distributed Lag (ARDL) cointegration framework. Data were retrieved from World Bank Development Indicators. Importantly, our findings reveal that EKC hypothesis does not exist. In addition, the long run models show that income and population appear to have significant impact on CO2 emission especially from solid fuel consumption and electricity and heat production. However, only population is revealed to promote CO2 from liquid fuel consumption. These findings suggest a dire need for Algeria to shift towards service intensive economy rather than resource intensive, and alternative renewable energy sources in order to mitigate environmental degradation as well as promote economic development. Keywords: Air Pollution; economic growth; environmental Kuznets curve hypothesis. JEL Classifications: O47; Q53; Q56